Content curation with social media in libraries - Guallar, Javier (Anuario ThinkEPI, 2016)
An analysis of how libraries curate content in social media platforms is discussed. The social media platforms that are analyzed are include Scoop.it, Paper.li, Flipboard, Storify, Milq, List.ly, Facebook, and Twitter; numerous examples are provided.
Keywords: Content curation; Content curator; Libraries; Public libraries; Academic libraries; Specialized libraries; Scholar libraries; Social media; Social networks; Pinterest; Scoop.it; Paper.li; Flipboard; Storify; Milq; List.ly; Facebook; Twitter